Comparison of Different DNA Extraction Methods in the Scope of the Sexual Biological Forensic Analysis - Íris da Rocha Carriço (2021)
Sexual assault is a public health issue that occurs on a global level, even though it is agreed within the forensic community that most cases do not get reported to authorities. Nevertheless, the ones that do get reported lead to the need of an investigation for the identification of the alleged abuser. The analysis of DNA samples found in the crime scene or in the victim's body is one of the most important evidence in these types of investigations. After being collected, the biological samples go through several phases until a genetic profile can be obtained: extraction, quantification, amplification, separation of STR fragments and genotyping. Whenever the quantity and quality of DNA present in the sample is enough, the identification of a genetic profile is possible; however, that is not always the case. In many cases of sexual assault, the DNA samples found do not have enough quantity of non-degraded genetic material from the abuser to be analyzed by all the currently used methods for these investigations, which creates a big challenge in this area. Therefore, the main goal of this master thesis was to perform an exploratory study in which different commercial extraction kits are used with samples mimicking the ones that can be found in sexual assault cases, so as to determine which one presents the best extraction efficiency in this context. In order to establish a more efficient workflow for forensic genetics analysis, the extraction step was followed by real-time PCR quantification, PCR amplification and electrophoresis detection. To fulfill the main goal of this master thesis, the commercial DNA extraction kits PrepFiler Express(r) and CaseWork Direct were used with samples including different types of biofluids (semen, blood and saliva), different types of matrices (denim, elastane, acrylic, polyester, cotton, jersey and filter-paper cards), some of which suffering different types of wash (with detergent or bleach). The comparison between the samples extracted with the two kits showed that PrepFiler Express(r) produces better quantification (in 91% of the samples) and amplification (1.3 times more complete genetic profiles) results, and original stains of semen and blood are the best types of samples to extract DNA from. The type of matrix was the least important factor when comparing extraction efficiencies, and there was no significant difference between the two kits for reference samples. Although more data is necessary, due to its quicker extraction time and lower cost, CaseWork Direct could be a good alternative for the extraction of reference samples.